Real-World Data to Document the Use of Herbal Medicinal Products in Children – Report of a Workshop in Krakow - Symma, Nico; Hensel, Andreas; Roether, Bernd; Steinhoff, Barbara; Bauer, Rudolf (Planta Medica, 2025)
The workshop “Real-world data to document the use of phytopharmaceuticals in children” was organized by the GA Foundation Plants for Health in collaboration with multiple international scientific societies on July 14, 2024, during the International Congress on Natural Products Research in Kraków, Poland. The event focused on leveraging real-world data and real-world evidence to support the use of herbal medicinal products (syn. phytopharmaceuticals) in pediatric care. The workshop aimed to discuss the current state and future approaches for utilizing real-world data/real-world evidence in expanding the use of herbal medicinal products in children and adolescents. Therefore, the workshop highlighted the unmet needs and challenges in documenting the effectiveness and safety of herbal medicinal products in children and emphasized the coordinated exchange and collaboration among academia, industry, and regulatory authorities. After an e-symposium in May 2022 with more than 300 participants and an in-person workshop on this topic in Bonn in June 2023, this workshop in Krakow was the third event of its kind hosted by the Foundation Plants for Health. Participants concluded that interdisciplinary collaboration is highly needed to establish qualified methods of data collection and assessment of real-world data, e.g., establishing requirements to incorporate nonprescription herbal medicinal products into electronic patient records and registries that can be accessed by all stakeholders.
Keywords: children; phytotherapy; herbal medicinal products; real-world data; dosages